Effect of Electrodeposition Parameters on the Composition and Surface Topography of Nanostructured Coatings by Tungsten with Iron and Cobalt - Yar-Mukhamedova, G. Sh.; Ved, M. V.; Yermolenko, I. Yu.; Sakhnenko, N. D.; Karakurkchi, A. V.; Kemelzhanova, A. (Institute of Combustion Problems, Kazakhstan, 2020)
The electrodeposition of binary and ternary coatings Fe-W and Fe-Co-W from mono ligand citrate electrolyte has been investigated. The Fe-Co-W coatings were formed from electrolytes, which composition differs in the ratio of the concentrations of the alloying components and the ligand content. The investigation results indicate a competitive reduction of iron, cobalt and tungsten, the nature of which depends both on the ratio of electrolyte components, and electrolysis parameters. The effect of both current density amplitude and pulse on off time on quality, composition and surface morphology of the galvanic alloys was determined. Coatings deposited on a direct current with a density of more than 6.5 A/dm², crack and peel off from the substrate due to the inclusion of Fe (III) compounds containing hydroxide anions. The use of non-stationary electrolysis allows us to extend the working range of current density to 8.0 A/dm² and form electrolytic coatings of sufficient quality with significant current efficiency and the content of the refractory component. The presence of the Co₇W₆, Fe₇W₆, α-Fe, and Fe3C phases detected in the Fe-Co-W deposits reflects the competition between the alloying metals reducing from hetero-nuclear complexes. The surface of binary and ternary coatings is characterized by the presence of spherical agglomerates and is more developed in comparison with steel substrate. The parameters Ra and Rq for electrolytic alloy Fe-W are of 0.1, for Fe-Co-W are 0.3, which exceeds the performance of a polished steel substrate (Ra = 0.007 and Rq = 0.010). These properties prospect such alloys as a multifunctional layer are associated with structural features, surface morphology, and phase composition.